THE EFFECT OF CAR, SIZE, CKPN, NPF ON FDR BUS WITH TPF AS INTERVENING VARIABLES IN 2016-2021 - Zan Ana Rizky; Anton Bawono (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
This study was conducted to know the effect of CAR, Size, CKPN, and NPF on Sharia Banking FDR with TPF as the intervening variable BUS in 2016-2021. This type of research uses quantitative with multiple regression analysis as data analysis sourced from secondary data. The model selected in this study uses panel data in the form of Fixed Effect Model annual data of CAR, Size, CKPN, NPF, TPF, and FDR recorded in BUS for the 2016-2021 period. The research data obtained were analyzed using the Eviews 10 application tool. The results of the research conducted by data processing showed that the TPF variable had a negative and significant effect on FDR. Variables CAR, Size, CKPN, and NPF have no significant effect on FDR. Then the Size variable has a positive and significant effect on TPF, while the CAR, CKPN, and NPF variables have no significant effect on TPF. After performing path analysis, the TPF variable can mediate the effect of Size on FDR. And the TPF variable cannot mediate the effect of CAR, CKPN, and NPF on FDR.. Keywords: CAR, Size, CKPN, NPF, TPF, FDR